From Alkanes to Carboxylic Acids: Terminal Oxygenation by a Fungal Peroxygenase - Olmedo, Andrés; Aranda, Carmen; del Río, José C.; Kiebist, Jan; Scheibner, Katrin; Martínez, Angel T.; Gutiérrez, Ana (Angewandte Chemie, 2016)
A new heme–thiolate peroxidase catalyzes the hydroxylation of n‐alkanes at the terminal position—a challenging reaction in organic chemistry—with H2O2 as the only cosubstrate. Besides the primary product, 1‐dodecanol, the conversion of dodecane yielded dodecanoic, 12‐hydroxydodecanoic, and 1,12‐dodecanedioic acids, as identified by GC–MS. Dodecanal could be detected only in trace amounts, and 1,12‐dodecanediol was not observed, thus suggesting that dodecanoic acid is the branch point between mono‐ and diterminal hydroxylation. Simultaneously, oxygenation was observed at other hydrocarbon chain positions (preferentially C2 and C11). Similar results were observed in reactions of tetradecane. The pattern of products formed, together with data on the incorporation of 18O from the cosubstrate H218O2, demonstrate that the enzyme acts as a peroxygenase that is able to catalyze a cascade of mono‐ and diterminal oxidation reactions of long‐chain n‐alkanes to give carboxylic acids. Eine Peroxygenase aus dem Pilz Marasmius rotula katalysiert eine Kaskade von mono‐ und diterminalen Oxygenierungen langkettiger n‐Alkane zu Carbonsäuren mit H2O2 als einzigem Kosubstrat (siehe Schema). Dank seiner selbständigen Monooxygenase‐Aktivität und der Fähigkeit, die am wenigsten reaktiven terminalen Positionen zu hydroxylieren, hat dieser Peroxygenase‐Typ große Vorteile im Hinblick auf eine milde Alkanaktivierung.